2010
DOI: 10.1186/1744-8603-6-11
|View full text |Cite
|
Sign up to set email alerts
|

Health and historical levels of freedom

Abstract: BackgroundThe link between political freedom and health is unclear. We aimed to determine the association by exploring the relationship of historical and cumulative freedom levels with important health outcomes.MethodsWe obtained countrywide health indicators for life expectancy, infant mortality, maternal mortality ratio, % low birth weight babies, Gini coefficient (a measure of wealth inequality) and various markers of freedom based on political rights and civil liberties. We applied multivariable logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Autocratic regimes generally appear to concern themselves only with the more powerful segments of the population (see Zweifel & Navia, 2000). Countries with more democratic governments (vs. more authoritarian governments) tend to have lower infant or child mortality rates (e.g., Biggs et al, 2010; McGuire, 2013).…”
Section: Background Literaturementioning
confidence: 99%
“…Autocratic regimes generally appear to concern themselves only with the more powerful segments of the population (see Zweifel & Navia, 2000). Countries with more democratic governments (vs. more authoritarian governments) tend to have lower infant or child mortality rates (e.g., Biggs et al, 2010; McGuire, 2013).…”
Section: Background Literaturementioning
confidence: 99%
“…Our conceptualization of these two indicators as health determinants is consistent with existing studies that have found increases in political freedom are associated with improvements in population health. 23,24…”
Section: Methodsmentioning
confidence: 99%
“…Our conceptualization of these two indicators as health determinants is consistent with existing studies that have found increases in political freedom are associated with improvements in population health. 23,24 GDP per capita is added in adjusted models to factor out different levels of economic development of East and Southeast Asian nations for a given year. Data are in constant 2005 U.S. dollars and retrieved from the World Bank.…”
Section: Independent Measuresmentioning
confidence: 99%